Performance & financing of micro, small and medium enterprises (MSMES) in Nigeria : implication of transaction costs and collateral - Ajuwon, Oluseye Samuel (Stellenbosch : Stellenbosch University, 2019)
Stellenbosch University. Faculty of Economic and Management Sciences. University of Stellenbosch Business School.